Histopathological Mapping of Meningiomas: A 10-year Retrospective Analysis - Pant, Ishita; Chaturvedi, Sujata; Sarma, Pragyan; Singh, Gurbachan (Indian Journal of Neurosurgery, 2021)
Background Meningiomas are a group of neoplasms showing a spectrum of histopathological variants, mostly corresponding to World Health Organization (WHO) grade I. However, certain histologic variants correspond histologically to WHO grades II and III. In this study, the histopathological spectrum of the meningiomas received in our department over the past 10 years is being revisited, with the aim to analyze the various histopathological variants, in order to assess their grade as per WHO 2016 criteria and also assess their epidemiology and localization.Materials and Methods A retrospective analysis of the histopathology records and clinical case files was done in 302 cases of histopathologically diagnosed cases of intracranial/intraspinal meningiomas (WHO grade I, II and III) received over a period of 10 years in our department. Hematoxylin and eosin (HE) staining was done for histological typing and grading of the tumors, and the cases were analyzed as per WHO 2016 criterion. Age and sex distribution along with the localization of the 302 cases was also analyzed.Results Among these, grade I meningiomas (93.05%) were the most common. According to histopathological type, transitional meningioma (76.50%) was the most common. Maximum cases were located at the cerebral convexities, reported in the fifth decade with a female preponderance.Conclusion As per WHO 2016, grade I meningiomas are associated with low-risk of recurrence and aggressive behavior, while WHO grade II and III meningiomas are associated with greater likelihood of recurrence and aggressive behavior. This classification itself summarizes the importance of accurate typing and grading of meningiomas on histopathology.
Keywords: Meningioma; WHO grade; histopathological variant